Genre, language and legitimation in complementary and alternative medicine promotional brochures - Goh, Ching Fen (2018)
As indicated by the label “complementary” and “alternative” accorded it, complementary and alternative medicine (CAM) as a field in the healing arts occupies the less desirable position of “the Other”, a position at the periphery of legitimate mainstream medicine also known as conventional or allopathic medicine. The peripheral position of CAM as opposed to the central position of conventional medicine is not least due to unresolved issues in CAM pertaining to regulatory controls, safety, consistency, and scientifically verifiable results, all of which are the mainstay of conventional medicine. Despite its weaker position as an option to healing, CAM has gained a large following among the health seeking public. The increasing popularity and commercial success of CAM in the health industry necessitates a closer attention to how CAM legitimizes its product claims and services in the marketing of health products. In the legal framework, conventional medicine is prevented from indulging in any kind of advertising or public promotional activities. However, for CAM, product promotion is allowed, and hence the promotional discourse of CAM products would be the site where product claims and services are actively constructed as legitimate, and defended, in view of counter-discourses surrounding its legitimacy. The study seeks to discover how CAM is legitimized through the use of genre and language in the promotional brochure, a specific type of text used for product marketing. Specifically, the research addresses the following questions: 1) How are generic structure and language used to promote health care products in CAM brochures?; 2) What ideologies about health and medicine are constructed in the text?; 3) How are the discourses of marketing/advertising and medicine appropriated in the commercial product marketing of CAM?; and 4) How do the discourse elements in the brochures work to legitimize CAM products in the face of oppositional discourses questioning CAM's position as legitimate medicine? Using a combination of critical discourse and genre analysis frameworks, the study advances a critical perspective of the practice of the marketing of CAM health care products. The findings of the present study reveal that CAM promotional brochures are represented by six compulsory moves and two optional moves. Each of the moves and steps used in the generic structure of CAM brochures are intentional to help serve the different communicative purposes, in promoting CAM products. Also, the present study reveals thirteen themes emerging from the lexical analysis to show how selective lexical words can be used to combine the ideologies of both ‘Science’ and ‘Nature’ to legitimize CAM focusing on natural properties in healing. The interdiscursive practices of science and nature are found evident through the appropriation of the discourse of medicine into the marketing/advertising discourse of CAM products, which aim to increase the perception of reliability, credibility and legitimation of CAM health care products. The present study also highlighted some defensive strategies employed in CAM promotional texts in the attempt to silence criticisms from CAM’s opponents to secure CAM’s legitimation in the health care industry.